A Novel Approach for Sentiment Classification on - Sai Ravi Teja, CH.; S., Stewart Kirubakaran (International Journal of Psychosocial Rehabilitation, 2020)
Sentiment analysis is the energetic region of research that focuses on analyzing the opinions or feelings of customers and classifying them into high-quality or bad reviews. In this paper, we endorse a new strategy for sentiment classification that critiques the usage of the map minimize concept. As we are conscious that in this technology of massive data, tremendous data/reviews are gathered through social media web sites at different areas that are distributed. Existing structures of Indian railways don’t classify and analyze the evaluations into superb and negative sentiments. Also, there is no automated classification of departments based upon the complaints or reviews acquired for further action. We address this trouble by creating a novel approach for sentiment classification using the map limit framework.